Do the training system and spacing affect the productivity and quality of tomato plants? (Research, Society and Development, 2022)
The determined growth tomato plant has advantages such as reduction of labor and inputs, enabling the production of fruits for consumption " in natura" efficiently. The objective of this work was to evaluate the conduction and spacing systems between plants with determined tomatoes and their influence on the production attributes and quality of the fruit. The experiment was carried out in the open field with three conduction systems (“half stake”, open V and “mulch”) and four spacings between plants (0.2; 0.3; 0.4; and 0.5 m). It was found that the highest yield and commercial production and number of large fruits were obtained in the half stake and mulch system. The spacing at 0.5 m provided the highest fruit production (6.4 kg in 56 fruits), and at 0.2 m, the highest productivity was obtained (145.63 t ha -1). In the 0.2 m and open V 0.5 m stake system, the fruits had a high lycopene content. spacing 0.2 m in half stake, and mulch systems were favorable for the production of quality fruit.